AB0776 18F-Fluoride PET/CT for Detection of Axial Involvement in Ankylosing Spondylitis. (9th June 2015) - Idolazzi, L.; Vantaggiato, E.; Salgarello, M.; Perandini, S.; Fassio, A.; Povino, M.R.; Fracassi, E.; Viapiana, O.; Gatti, D.; Rossini, M.; Adami, S.
Abstract : Background: In ankylosing spondylitis (AS) the various degree of bone erosions is associated with extensive new bone formation, involving typically the edges of the cartilage structures, particularly where the enthesis insert. Magnetic resonance imaging (MRI) is considered the "gold standard" imaging modality for the detection of inflammatory processes and of "bone oedema" and validated scoring methods have been developed. However, new bone formation (e.g.: syndesmophyte formation) ensuing in irreversible bone deformation and disability can be detected only after years of disease and little is known on the effectiveness of available therapies for its prevention. Objectives: The [18F]fluoride isotope is a bone-specific tracer that during bone remodelling is incorporated into the skeleton at sites of active osteoblastic bone synthesis, and thus representing bone synthetic activity. 18F-fluoride PET/CT (F-PET/CT) provides also high spatial resolution and sensitivity. The role of F-PET/CT in the detection of axial involvement in ankylosing apondylitis is not known. Methods: We studied by F-PET/CT 29 AS patients aged 26 to 69 years referred to the Nuclear Medicine Unit (Saro Cuore Hospital, Negrar, Verona, Italy) by the Rheumatology Unit of the University of Verona. The clinical assessment included BASFI, a disability index, and ASDAS which reflects disease activity: pain and inflammation. The number of regions of high bone turnover [18F uptake] or CT osteoarthritis features at the spine and at the 2 sacroiliac joints was counted. Results: The number of F-PET/CT positive sites was significantly higher in patients with severe functional impairment and higher disease activity and it was positively related to both BASFI (r=0.339; P=0.036) and ASDAS (r=0.408; P=0.014) while the number of degenerative features (osteoarthritis) was related neither with functional impact nor with disease activity. A strong relation was also found between the localization of F-PET/CT positive and of pain sites. Interestingly F-PET positive sites were detected in 6 out of 9 patients with a ASDAS <1.3 and considered in disease remission. Conclusions: In conclusion F-PET/CT in AS patients with a single examination accurately identify the functional impairment and the clinical involvement of AS. Its value in predicting new abnormal bone formation and functional worsening requires prospective long term studies. Disclosure of Interest: None declared